Estimation of Population Mean in the Presence of Missing Data Under Stratified Random Sampling - دريباتي محمد; بوبو منذر; درويش هديل (Latakia University Journal -Basic Sciences Series, 2021)
This paper aims to propose a new estimator of the population mean in stratified random sampling with missing data. The missing values studied by the paper are measurement errors and non-response errors together and at the same time. To study the effectiveness of the proposed estimator, the results obtained from this estimator were compared with several previous estimates that were previously mentioned in scientific studies. The results were compared between the different estimates on both generated and real data, and the bias error and mean squares of error were compared for each of them.